Healthcare Utilization and Quality of Life Improvement after Ablation for Paroxysmal AF in Younger and Older Patients. Issue 4 (3rd March 2017) - BIVIANO, ANGELO B.; HUNTER, TINA D.; DANDAMUDI, GOPI; FISHEL, ROBERT S.; GIDNEY, BRETT; HERWEG, BENGT; OZA, SAUMIL R.; PATEL, ANSHUL MAHENDRA; WANG, HUIJIAN; POLLAK, SCOTT J.
Abstract : Background: Atrial fibrillation (AF) prevalence increases significantly with age. Little is known about the effect of AF ablation on quality of life and healthcare utilization in the elderly. The objective of this study was to quantify the healthcare utilization and quality of life benefits of catheter ablation for AF, for patients ≥65 years compared to patients <65 years. Methods: Two multicenter U.S. registry studies enrolled patients with paroxysmal AF. Baseline characteristics and acute outcomes were collected for 736 patients receiving catheter ablation with the Navistar ® Thermo Cool ® SF Catheter (Biosense Webster, Inc., Diamond Bar, CA, USA). Healthcare utilization and quality of life outcomes were collected through 1 year postablation for 508 patients. Results: The rates of acute pulmonary vein isolation were high and similar between patients ≥65 years and <65 years (97.5% vs 95.8%, P = 0.2130). Length of stay for the index procedure was similar between age groups with 82.2% of the older group and 83.2% of the younger group having one‐day hospitalization. Disease‐specific quality of life instrument scores improved significantly and similarly for older and younger patients at 1 year postablation, compared to baseline. AF‐related hospitalizations and emergency department visits were similar or lower in older patients compared to younger patients, as reported at 1 year postablation. Conclusion: For older patients undergoing catheter ablation for paroxysmal AF, healthcare utilization parameters were lower or not significantly different than for younger patients, and quality of life outcomes were similarly improved. These findings support the use of catheter ablation as a treatment option in older patients with paroxysmal AF.